THE USE OF DIARY WRITING TO IMPROVE EIGHT GRADE STUDENTS’ WRITING SKILL AT SMPN 3 MALANG - Euis Fauziah Ramadhani; Riski Lestiono (Erudio Journal of Educational Innovation, 2015)
The research was focused on solving the problems in a classroom and finding out that the diary writing can improve the students’ writing achievement. The research was classroom action research which was conducted in two cycles. The subjects of this research were eight grade students of SMPN 3 Malang, VIII-1 class with total number of students 32. Diary writing was the treatment that had been given during 2 cycles. Additionally, the instruments to collect the data were test and observation field notes. After implementing the diary writing in two kinds of text, descriptive and recount, and analysing the collected data, it is found that the students’ score gradually improved specifically when they wrote recount text. Besides, the changing topics in every meeting were needed to make the students more interested in writing. The researchers found two weaknesses at the first cycle; those were students’ lateness in submitting their diaries which made the researcher also late in giving the feedbacks, and the students’ limited vocabulary which made them tend to use simple sentences and the same vocabularies. Dealing with those weaknesses, the researchers used award strategy. The researchers provided different emoticon stickers that rewarded the students’ punctuality and creativity. In addition, the researchers also conducted a pair work writing activity in the second cycle in order to make the students learn from their friends.Key words: Diary Writing, Writing Skill, SMPN 3 Malang